FOLFIRINOX or gemcitabine/nab‐paclitaxel in advanced pancreatic adenocarcinoma: A novel validated prognostic score to facilitate treatment decision‐making in real‐world. Issue 3 (22nd September 2022) - Marschner, Norbert; Hegewisch‐Becker, Susanna; Reiser, Marcel; von der Heyde, Eyck; Bertram, Mathias; Hollerbach, Stephan H.; Kreher, Stephan; Wolf, Thomas; Binninger, Adrian; Chiabudini, Marco; Kaiser‐Osterhues, Anja; Jänicke, Martina; et al.
Abstract: There is no prospective, randomised head‐to‐head trial comparing first‐line FOLFIRINOX and gemcitabine/nab‐paclitaxel in advanced pancreatic cancer. We assess real‐world effectiveness and quality of life (QoL) of both regimens using a new prognostic score. This analysis includes 1540 patients with advanced pancreatic cancer from the prospective, clinical cohort study Tumour Registry Pancreatic Cancer separated into learning (n = 1027) and validation sample (n = 513). The Pancreatic Cancer Score (PCS) was developed using multivariate Cox regression. We compared overall survival (OS) and time to deterioration (TTD) for longitudinal QoL between first‐line FOLFIRINOX (n = 407) and gemcitabine/nab‐paclitaxel (n = 655) according to patients' prognostic risk, after inverse probability of treatment weighting (IPTW) by propensity score analysis. The PCS includes nine independent prognostic factors for survival: female sex, BMI ≥24/unknown, ECOG performance status ≥1, Charlson comorbidity index ≥1, tumour staging IV/unknown at primary diagnosis, liver metastases, bilirubin >1.5× upper limit of normal (ULN), leukocytes >ULN and neutrophil‐to‐lymphocyte ratio ≥4. Median OS of the validation sample was 11.4 (95% confidence interval [CI]: 10.4‐14.4), 8.5 (95% CI: 6.8‐9.6) and 5.9 months (95% CI: 4.0‐7.4) for favourable‐ (0‐3 risk factors), intermediate‐ (4‐5 factors) and poor‐risk group (6‐9 factors), respectively. After IPTW, only poor‐risk patients had significantly longer median OS and TTD of overall QoL with FOLFIRINOX (OS: 6.9 months, 95% CI: 3.9‐13.3; TTD: 10.6 months, 95% CI: 2.0‐14.1) vs gemcitabine/nab‐paclitaxel (OS: 4.0 months, 95% CI: 2.8‐4.8; TTD: 4.1 months, 95% CI: 2.4‐4.5). Our novel PCS may facilitate treatment decisions in clinical routine of advanced pancreatic cancer, since only poor‐risk, but not favourable‐risk patients, seem to benefit from intensified treatment with FOLFIRINOX. Abstract : What's new? Prospective, randomised head‐to‐head trials comparing first‐line FOLFIRINOX and gemcitabine/nab‐paclitaxel in advanced pancreatic cancer are lacking. Here, real‐world data on more than 1000 patients from the prospective German TPK clinical cohort study suggest that only patients stratified as having a poor survival risk by a newly developed prognostic score may benefit from intensified treatment with FOLFIRINOX. Poor‐risk patients had significantly longer median overall survival and time‐to‐deterioration of overall quality of life with FOLFIRINOX vs gemcitabine/nab‐paclitaxel, after standardising treatment groups using a propensity score. The novel prognostic score may facilitate treatment decisions in the routine clinical management of advanced pancreatic cancer.